Perbandingan Implementasi Kurikulum Montessori pada Jenjang Sekolah Dasar Negeri dengan Swasta - Nabila Hafizhotul Millah; Sofyan Iskandar; Primanita Sholihah Rosmana; Lathifah Dewi Anjani; Salma Ramadhani Putri (Universitas Negeri Surabaya, 2022)
ABTRACT Each school has a different curriculum implementation according to the vision and mission of the school. One of the curricula that are applied at the elementary level is the Montessori curriculum, which in its approach focuses on practical life, sensory, mathematics, language, music, art, and culture. This research was conducted to find out how the implementation of the Montessori curriculum at the public elementary school level compares with private elementary schools. This research uses descriptive qualitative research. The results of this study reveal that the implementation of the Montessori curriculum at the private elementary school level is much more effective than the implementation of the Montessori curriculum at the public elementary school level. This is evidenced that private elementary schools have facilities and infrastructure that strongly support the implementation of the Montessori curriculum in schools, because the schools receive funds from foundations and parents of students, while elementary schools only rely on funds channeled by the government so that in its implementation, public elementary schools are also less totality or effectiveness. ABSTRAK Setiap sekolah memiliki penerapan kurikulum yang berbeda sesuai dengan visi dan misi dari sekolah tersebut. Salah satu kurikulum yang diterapkan pada jenjang SD yaitu kurikulum Montessori, yang mana dalam pendekatannya berfokuskan pada practical life, sensorik, matematika, bahasa, musik, artistik, dan budaya. Penelitian ini dilakukan guna mengetahui bagaimana perbandingan implementasi kurikulum Montessori pada jenjang Sekolah Dasar negeridengan Sekolah Dasar swasta. Penelitian ini menggunakan penelitian deskriptif kualitatif. Hasil dari penelitian ini mengungkapkan bahwa implementasi kurikulum Montessori pada jenjang Sekolah dasar swasta jauh lebih efektif dibandingkan dengan pengimplementasian kurikulum Montessori pada jenjang Sekolah Dasar negeri. Hal tersebut dibuktikan bahwa sekolah dasar swasta memiliki sarana dan prasarana yang sangat mendukung penerapan kurikulum Montessori di sekolah, karena pihak sekolah menerima dana dari yayasan dan orangtua peserta didik, sedangkan Sekolah Dasar hanya mengandalkan dana yang disalurkan oleh pemerintah, sehingga dalam penerapannya pun Sekolah Dasar negeri kurang totalitas atau efektif.